Counselling Services For Peace and Unity Awareness Among Youths in Niger State - Mamman, Ruqayyat Momoh; Abubakar, Lukman Zuba; Sarki, Isah (Universitas Mercu Buana Yogyakarta, 2022)
This study investigated the role of counselling services for peace and unity awareness among youths in Minna metropolis of Niger State. Descriptive survey research was employed to collect information from the sample and conclude base on the targeted population. The population was all youth in Minna metropolis, four wards were randomly selected at twenty youths per ward, eighty youths were used for the sample. The instrument used were the tagged Questionnaire for counselling services for peace and unity awareness among youth (QCSPUAY). It was meant to measure causes of crisis, disunity, place of youth on peace and unity in our communities and the role of counsellors in creating awareness among youth in Minna metropolis. A finding of the study showed that there is severe disunity amongst the youth and that youth play a great role in influencing peace and unity in their various communities. Hence, for the sake of peace and unity, there is an urgent need for counselling services in all forms of education to expose youth to see tremendous advantages of peace and unity. Therefore, the study recommended that youth of different tribes, religions, political affiliations and social-economic status should always pursue peace and unity wherever they found themselves. Also, the services of counsellors should focus on creating awareness that will assist in influencing youth towards embracing peace and unity.Â